Richard Newhauser (2023): Por una Edad Media sensorial: aportes de Richard Newhauser. Ed. de Gerardo Fabián Rodríguez y Lidia Raquel Miranda; trad. de Carlos Rafael Domínguez y María Emilia García Miranda. Mar del Plata: Universidad de Mar del Plata. 355 pp. ISBN: 978-987-811-082-0 - Cases Pérez, Carlos (Revista de Filología Románica, 2025)